2021
DOI: 10.1186/s12876-021-01679-8
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and survival of infants with congenital duodenal obstruction following Kimura procedure with post-anastomosis jejunostomy feeding tube

Abstract: Background Several modifications of the Kimura procedure for congenital duodenal obstruction (CDO) have been reported, however, their effects on the outcomes show conflicting results. Methods We compared the CDO outcomes following the Kimura procedure with and without post-anastomosis jejunostomy feeding tube (JFT). Results A total of 52 CDO neonates were involved (JFT: 13 males and 2 females vs. non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In total, 70 studies with a total of 4169 patients described the type of DO (Fig. 3 ) [ 1 , 6 , 10 12 , 16 19 , 21 25 , 27 32 , 34 52 , 54 57 , 59 , 62 65 , 67 , 70 75 , 81 83 , 85 , 89 , 90 , 93 95 , 98 100 , 102 , 105 , 106 ]. Type 3 DO consisting of complete atresia, was the most frequent obstruction and occurred in a pooled percentage of 54% of patients with DO (95% CI 0.478–0.603; I 2 = 88%; p < 0.001) of the children.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 70 studies with a total of 4169 patients described the type of DO (Fig. 3 ) [ 1 , 6 , 10 12 , 16 19 , 21 25 , 27 32 , 34 52 , 54 57 , 59 , 62 65 , 67 , 70 75 , 81 83 , 85 , 89 , 90 , 93 95 , 98 100 , 102 , 105 , 106 ]. Type 3 DO consisting of complete atresia, was the most frequent obstruction and occurred in a pooled percentage of 54% of patients with DO (95% CI 0.478–0.603; I 2 = 88%; p < 0.001) of the children.…”
Section: Resultsmentioning
confidence: 99%
“…The following period between 2000 and 2009 included 17 studies with 970 patients and had a calculated pooled proportion of 32% percent (95% CI 0.243–0.407; I 2 = 82%; p = 0.000) [ 12 , 14 , 22 , 23 , 28 , 29 , 37 , 45 , 48 , 49 , 62 , 67 , 73 , 74 , 85 , 90 , 106 ]. The last period between 2010 and present included 47 studies with 3747 patients [ 1 , 6 , 16 , 18 21 , 24 27 , 31 , 35 , 36 , 42 , 46 , 47 , 50 , 52 , 53 , 55 , 57 59 , 68 , 69 , 71 , 72 , 77 , 78 , 81 84 , 87 , 88 , 91 95 , 97 , 98 , 100 , 103 105 ]. For this period, the pooled percentage for cardiac anomalies was 34% percent (95% CI 0.290–0.392; I 2 = 89%; p = 0.000).…”
Section: Resultsmentioning
confidence: 99%
“…LOS in this study is in the lower range of what is reported from recent studies on CDO. 1,15,23 This suggests that also other institutions have been unsuccessful in reducing LOS in this patient population. The main factors keeping CDO patients in the hospital are the time to achieve full oral feeds and postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Duodenoduodenostomy or Kimura’s procedure is often described as the surgery of choice for duodenal stenosis, introduced in 1977. Kimura described a method to bypass the stenosis by applying a diamond-shaped side-to-side duodenoduodenostomy [ 4 ] with good outcomes for congenital duodenal obstruction [ 5 ]. Some variation was also described later on with the introduction of post-anastomosis jejunostomy feeding and more recently the inverted duodenoduodenostomy (i-DSD) [ 6 ], but the main gist of the surgical procedure is to bypass the stenosis segment.…”
Section: Discussionmentioning
confidence: 99%